Development of language skills through didactic subtitling: a systematic review - Olivia Correa Larios (Universidad de Guadalajara, 2022)
This article presents a systematic review of the literature on the use of subtitling in the teaching of foreign languages in university contexts in the last five years. First, the conceptual framework of audiovisual translation for didactic purposes, its classification and influence on the development of linguistic skills are presented, then the methodology used for the search and compilation of studies. Considering the inclusion and exclusion criteria, fourteen empirical studies were selected and then distributed into four sections according to the type of subtitling they address: intralinguistic, standard interlinguistic, inverse interlinguistic and mixed modalities. The results show that subtitling enhances the acquisition of vocabulary, oral comprehension, oral production and grammatical understanding in foreign languages. In addition, participants report a good reception of the subtitling task.